Aberrant type 2 dopamine receptor availability in violent offenders with psychopathy - Lukkarinen, Lasse; Tuisku, Jouni; Sun, Lihua; Helin, Semi; Karlsson, Henry K.; Venetjoki, Niina; Salomaa, Marja; Rautio, Päivi; Hirvonen, Jussi; Lauerma, Hannu; Tiihonen, Jari; Nummenmaa, Lauri (Academic Press, 2025)
Psychopathy is characterized by antisocial behavior, poor behavioral control and lacking empathy, and structural alterations in the corresponding neural circuits. Molecular brain basis of psychopathy remains poorly characterized. Here we studied type 2 dopamine receptor (D2R) and mu-opioid receptor (MOR) availability in convicted violent offenders with high psychopathic traits (n=11) and healthy matched controls (n=17) using positron emission tomography (PET). D2R were measured with radioligand [11C]raclopride and MORs with radioligand [11C]carfentanil. Psychopathic subjects had lowered D2R availability in caudate and putamen, and striatal D2R availability was also associated with degree of psychopathic traits in this prisoner sample. No group differences were found in MOR availability, although in the prisoner sample, psychopathic traits were negatively correlated with MOR availability in the amygdala and nucleus accumbens. We conclude that D2R signaling could be the putative neuromolecular pathway for psychopathy, whereas evidence for alterations in the MOR system is more limited.